Nexus Between FDI and Tourism: Empirical Evidence from Asian Countries - Paul, Sujan Chandra; Deb, Santus Kumar; Hossain, Md Abir; Saha, Mallika (Asian Journal of Economic Modelling, 2022)
This research aims to look into the impact of foreign direct investment on tourism. Panel data from 46 Asian countries between 1998 and 2018 were collated for this study. The OLS, POLS, 2SLS, and GMM models were used in this study. A substantial correlation was found between between foreign direct investment and the number of international tourist departures in all models except the POLS model, and with the exception of the GMM model, there was a significant negative association between foreign direct investment and international tourism spending. In the POLS model, there is a significant positive relationship between foreign direct investment and international tourism receipts for passenger transport items, as well as expenditures for passenger transport items and international tourism receipts, and a significant negative relationship between foreign direct investment and international tourism receipts for passenger transport items. In the 2SLS model, there is a significant positive relationship with international tourism receipt. In the GMM model, there is a significant positive relationship between foreign direct investment and international tourism and a significant negative relationship between foreign direct investment and international tourism receipt, expressed in percentage of total exports.